O estado da Paraíba na mira do Serviço Nacional de Informações (SNI) : sindicatos urbanos sob vigilância (1979-1987) - Costa, Matheus Pereira da (2023)
Aligned with the New Political History, this study aims to analyze the surveillance carried out by the National Information Service (SNI) on urban unions in the state of Paraíba between 1979 and 1987. Surveillance is understood as an intrinsic element of the National Security State, structured in the first year of the civil-military coup, and aimed at controlling economic development and labor mobilization. By focusing on the reports produced by the Service agents, the objective is to understand the creation of the repressive apparatus and its structuring throughout the military dictatorship, with the establishment of regional agencies in the main capitals of Brazil, the composition of its officers, and the territorialization of the Service's power in the state of Paraíba. It also seeks to understand the logic behind the production of repression reports, imbued with an authoritarian political culture and an anti-communist imaginary. Finally, this study also contributes to the history of the labor movement in Paraíba by seeking to expose, through the analysis of the reports, situations and influential leaders in the struggles of the working class in the territory. The main documentary corpus used for this research consists mainly of the SNI - Recife Agency Archive.